MODEL VISUALISASI INFORMASI DASHBOARD PADA PEMETAAN TANAMAN OBAT DAN LANGKA KABUPATEN KEDIRI MENGGUNAKAN MICROSOFT POWER BI - Heru Stiawan; M Najibuloh Muzzaki; Sucipto; Anita Sari Wardani; Rina Firliana; M Iqbal Khalid; Adhi Wicak Milbar Gamas; Shandy Arshad Busro (Jurnal Informatika Teknologi dan Sains, 2022)
The mapping of medicinal and rare plants in Kediri Regency is a collaborative program between Balitbangda and Universitas Nusantara PGRI Kediri. In its implementation there are problems related to plant information that has been collected. In solving this problem, a solution is proposed by using an analytical approach and also visualizing information into a dashboard. The output of this research is a dashboard visualization that is used for reports and information to the implementing team of the cooperation program for mapping medicinal and rare plants. For the tools used in Microsoft Power BI, use charts and cards in the dashboard visualization